The Library of Congress Civil War desk reference - Wagner, Margaret E.; Gallagher, Gary W.; Finkelman, Paul, 1949-; Library of Congress (New York : Simon & Schuster, 2002)
From the home of The Nation's Memory comes the ultimate one-volume reference on the Civil War. Features include a timeline of the war with important political, military, and social events; biographies of important figures; and concise coverage of major campaigns and battles. 100 photos. 38 maps. The bloody conflict that sundered the United States from 1861 to 1865 took 620,000 lives, laid waste to large sections of the American South, and decided the future course of the nation. Its reverberations are still felt in American life. Now from the home of The Nation's Memory comes The Library of Congress Civil War Desk Reference. Drawn from the Library's unparalleled Civil War collections-including previously unpublished letters and diaries, maps and photographs, as well as thousands of works by post-Civil War scholars and experts-this is the ultimate one-volume reference on the Civil War. A comprehensive yet accessible compendium, The Library of Congress Civil War Desk Reference is organized into chapters that address broad themes such as Antebellum America, Wartime Politics, Armies, and Reconstruction and Aftermath of the War. Each of these chapters includes more specific topics, such as The Election of 1860, Notable Civil War Officers, and African Americans During Reconstruction. There are timelines that chronicle major events, brief profiles of significant people, and excerpts from key pieces of legislation and addresses that reflect the passions and politics of the times. Here readers can find, for example, detailed information on the arms used on both sides during the Civil War in the Weaponry chapter. And descriptions of significant battles, as well as information on casualties, military strategy and tactics, and logistical support, are to be found in the Battles and the Battlefield chapter. Topics ranging from economic conditions north and south of the Mason-Dixon line on the eve of the war to the history of slavery in the United States to the impact of the Civil War on literature and the fine arts give additional depth and context to the book's presentation of Civil War events. The Library of Congress Civil War Desk Reference also looks beyond the major events and figures and examines the lives of the common soldiers (from their diet, training, and medical treatment to the struggles of the Union's black soldiers), the various roles women played in the war, and telling events on the home fronts. Along with the words of writers such as Walt Whitman and Herman Melville, readers will find excerpts from the journals and letters of nurses, soldiers, refugees and freedmen. A final chapter offers a guide to further study of the Civil War-including information about major archival collections, important published resources, and national historic sites-for those who wish to learn more. Prodigious in its scope, illustrated with more than 100 photographs and drawings and dozens of maps, The Library of Congress Civil War Desk Reference is sure to become the indispensable one-volume reference on the Civil War. Wagner's (Library of Congress), Gallagher's (history, U. of Virginia), and Finkelman's (law, U. of Tulsa) guide is organized thematically into 13 main chapters, each further divided into several topics. A detailed table of contents and 38-page subject index make this an easy text to use. It is also unique in its inclusion of subjects generally absent in other works, such as the contributions of topographical engineers and mapmakers, and developments in surgery and medical care. Illustrated with some 100 photographs, drawings and maps, this academic text is accessible to general readers interested in American history and the Civil War.
Civil War time line -- Antebellum America -- Wartime politics -- Battles and the battlefield -- The armies -- Weaponry -- The war on the water -- Prisons and prisoners of war -- Medical care and medicine -- The home front -- Reconstruction and the aftermath of the war -- The Civil War in literature and the arts -- Studying the war: research and preservation.
"A Grand Central Press book."
Includes bibliographical references and index.
Keywords: United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Chronology; 2